Numerical assessment of riverbank filtration using gravel back filter to improve water quality in arid regions - Abd-Elaty, Ismail; Saleh, Osama K.; Ghanayem, Hala M.; Zeleňáková, Martina; Kuriqi, Alban (Frontiers in Earth Science, 2022)
The main challenge of water resource management in high-stress regions, especially in developing countries, is in adopting non-traditional methods to obtain safe drinking water in desired quantities. In Egypt, the riverbank filtration (RBF) system is one of the most common solutions to solve rivers’ water quality issues. Several sites have been investigated, and the system has demonstrated tremendous potential. The drinking water plant in Embaba, Giza, Egypt, is considered in this study to improve the quality of the abstracted water through the vertical well system. The numerical code of MODFLOW and MT3D is used to simulate the impact of using the emplacement of the gravel-pack filter (GPF). Three different scenarios were investigated: the first consists of vertical GPF; the second is horizontal GPF for different geometries, depths, widths or thicknesses, lengths, and permeability of the filter material; and, the third is drilling a pipe filter through the riverbed for different pipe numbers, depths, and the material’s hydraulic conductivity. The results revealed that the riverbank filtration sharing (RBFS) rate was increased by increasing the filter width or thickness at the riverside, the filter pipe numbers, the length of the horizontal filter, and the permeability of filter material. At the same time, the thickness of the river bed decreased by increasing the filter width at the groundwater side. Also, the RBFS was increased by increasing the filter width or the thickness in the two directions and the pipe length. However, it returned to decrease again due to groundwater sharing. Thus, the RBF design should carefully consider the gravel-pack, pipe filter geometry, and permeability impact rate of RBFS.